Surgical Treatment of Intrapelvic Pseudotumour after Hip Resurfacing Arthroplasty: Case Report and Literature Review - Cristian Barrientos; Julian Brañes; José-Luis Llanos; Alvaro Martinez; Maximiliano Barahona (Case Reports in Orthopedics)
Hip replacement is the surgery of the last century due to its impact on the quality of life. A pseudotumour is a rare complication of hip arthroplasty, and it is related to a metal-bearing surface. Pseudotumour is a challenging scenario for hip surgeons due to poor clinical outcomes. The patient consulted for hip pain and paresthesia in the left lower extremity, and analyses showed that the cause was a sizeable intrapelvic pseudotumour. A multidisciplinary team surgery was planned. At first, an infraumbilical approach was made to resect the intrapelvic-retroperitoneum portion of the pseudotumour. Then, a posterolateral hip approach was performed, to resect the remaining portion of the pseudotumour and revision arthroplasty. At five years of follow-up, there are no clinical or imaging signs of recurrence of the pseudotumour. Treatment evidence is limited to a series of cases and expert opinions; we encourage complete resection and revision arthroplasty.